2020
DOI: 10.15244/pjoes/114507
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Modified Bentonite Clay as an Eco-Friendly Adsorbent for Landfill Leachate Treatment

Abstract: Historically, landfilling has been the oldest form of solid waste management around the world [1] and in many regions due to the simplicity of design and the low cost of operations, It is still the most common and popular solid waste management strategy [2]. Although this strategy of solid waste management has some advantages, it leads to the production of leachate [3] so that the production of highly contaminated leachate is known as one of the main weaknesses of this type of waste management [4]. Leachate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Sulfuric acid, which has a higher number of protons than the HCl used in this study and thus increases the clay's surface acidity, is the likely cause of the difference. Another study found a 92.1% reduction in the amount of turbidity when an amino acid-modified bentonite clay was used [ 42 ]. That being said, future research may find that sulfuric acid is an effective tool for achieving the recommended turbidity discharge limit.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfuric acid, which has a higher number of protons than the HCl used in this study and thus increases the clay's surface acidity, is the likely cause of the difference. Another study found a 92.1% reduction in the amount of turbidity when an amino acid-modified bentonite clay was used [ 42 ]. That being said, future research may find that sulfuric acid is an effective tool for achieving the recommended turbidity discharge limit.…”
Section: Resultsmentioning
confidence: 99%
“…Under optimal conditions, the maximum COD and turbidity removal for amino acid modified clay was 65.7% and 92.1%, respectively, under pH adjustment setups. Furthermore, the analysis showed that the adsorbent created under pH adjustment settings had a greater leachate treatment efficiency than the adsorbent synthesized under non-pH adjustment conditions (Hajjizadeh et al 2020).…”
Section: Other Nanomaterials Based Adsorbentsmentioning
confidence: 97%
“…Apart from carbon nanotubes, several other nano adsorbents were also reported for the treatment of leachates: nano-ionic copper doped oil palm frond activated carbon (n-OPFAC) (Adam et al 2019), Saccharum officinarum leaves (SL) assisted nano-silica (NS) (Kaliannan et al 2019), and others. Bentonite clay was modified with amino acids as an eco-friendly adsorbent (Hajjizadeh et al 2020). Adam et al prepared n-OPFAC.…”
Section: Other Nanomaterials Based Adsorbentsmentioning
confidence: 99%
“…It also affects the charges of the adsorbate and adsorbent in solution and the manner in which they interact with each other [19]. The pH of an aqueous solution has a significant impact on the degree of ionization and the behavior of several contaminants, which in turn affects the reaction kinetics and equilibrium of the adsorption process [20] .…”
Section: Effect Of Ph On Cod Tss and (Oandg) Removalmentioning
confidence: 99%